Advances in the study of the interaction between schistosome infections and the host's intestinal microorganisms - Ao Hong; Abdulrahim Umar; Hao Chen; Zheng Yu; Jing Huang (Parasites & Vectors)
Abstract Schistosomiasis, also called bilharziasis, is a neglected tropical disease induced by schistosomes that infects hundreds of millions of people worldwide. In the life cycle of schistosomiasis, eggs are regarded as the main pathogenic factor, causing granuloma formation in the tissues and organs of hosts, which can cause severe gastrointestinal and liver granulomatous immune responses and irreversible fibrosis. Increasing evidence suggests that the gut microbiome influences the progression of schistosomiasis and plays a central role in liver disease via the gut–liver axis. When used as pharmaceutical supplements or adjunctive therapy, probiotics have shown promising results in preventing, mitigating, and even treating schistosomiasis. This review elucidates the potential mechanisms of this three-way parasite–host–microbiome interaction by summarizing schistosome-mediated intestinal flora disorders, local immune changes, and host metabolic changes, and elaborates the important role of the gut microbiome in liver disease after schistosome infection through the gut–liver axis. Understanding the mechanisms behind this interaction may aid in the discovery of probiotics as novel therapeutic targets and sustainable control strategies for schistosomiasis. Graphical Abstract